FAKTOR RISIKO YANG BERHUBUNGAN DENGAN KEJADIAN COMPUTER VISION SYNDROME PADA PEGAWAI DI KANTOR PROYEK PEMBANGUNAN REVITALISASI HALTE BRT TRANSJAKARTA PAKET D (15 HALTE) TAHUN 2023 - Fitria Suci Rahmadhani (2023)
The use of digital devices has become an important part of everyday life. In addition to having a positive impact on its users, computers can also have a negative impact, especially in causing health problems such as CVS. The purpose of this study was to determine the relationship of risk factors to the incidence of CVS in employees at the Brt Transjakarta Stop Revitalization Development Project Office Package D (15 stops). This research used quantitative analytic research with a cross-sectional study design. The sample of this study was 52 respondents who were the population in this study. Data were analyzed using the chi-square test. The results showed that there was a relationship between the duration of computer use (p=0.015), monitor visibility (p=0.026), and lighting intensity (p=0.015) with computer vision syndrome, but there was no relationship between gender (p=0.178), age (p=0.242), length of service (p=1.000), and use of glasses (p=0.668) with the incidence of CVS. It is recommended for computer-using employees to apply the 20-20-20 rule as a preventive measure and adjust the display magnification on the computer monitor screen.